Exploratory Study and Analysis on Color Grading Technique for Horror Short Movie - Rayden Vebrianto; Jimmy Pratama (IJISTECH (International Journal of Information System and Technology), 2023)
Horror is a movie genre where the main purpose is to convey fear, anxiety, suspense, and such to the audiences. On ensuring the success of a horror movie, there is one big factor that decides it, which is color grading. Color grading is one of movies editing technique which main purpose is to change color in a video, useful to build or support a desired atmosphere. Color grading is important in horror movies because if the applied technique does not fit with the movie concept, the desired message to convey will fail to deliver. In this study, a two version of horror short movie will be produced, with one version using a darker color grading tone (A) and the other one uses brighter color grading tone (B). The method used in this study is Research & Development, with Research using semiotic analysis and Development using Multimedia Development Life Cycle (MDLC) method. The semiotic analysis will focus on 10 horror movies with a rating of at least 7 based on IMDb US Box Office Rating, and the analyzed subject is the color grading technique used on each movies. The color grading analysis result then will be applied to the short movie production. After the short movie production has been finished, a blind test will be carried out to see which version of color grading suits better with the movie. The blind test is carried out with 53 participants, and the result is 39 participants choosing A and the other 14 choosing B. Due to the significance difference, a reasoning was asked to the participants. Most of the participants who chose A said A fits more with the movie concept and for them B does not really convey the horror from the movie, while those who chose B just gave personal preference as an answer.